A new coil structure for positioning estimate of wireless power transmission. Issue 12 (23rd September 2020) - Zou, Ming Xuan; Cong, Zheng; Xu, Jin
Abstract: Accurate positioning is certainly essential in wireless power transmission (WPT) for the improvement of transmission efficiency. This article proposes a novel positioning coil structure for the WPT system, which determines the offset direction of the transmitter and receiver using the principle of mutual inductance. First, a new wireless positioning structure and parameters are designed. Then, the theoretical formulas are derived, which help to obtain the functional relationships between coils and distances. According to the various mutual inductances of the proposed positioning structure, how to determine the specific offset direction of the receiver is further discussed. Meanwhile, the intensity of the magnetic field between the transmitter and receiver is simulated. Finally, the hardware experiment platform is established to verify the theory. The simulation and experimental results show that the coil structure effectively realizes the determination of the load deviation direction. This method is of practical significance in realizing the precise positioning of the transmitter and receiver, which enable the creation of novel reconfigurable devices as potential applications.